THE DOUBLE-EDGED EFFECT OF CORPORATE GOVERNANCE: THE INTERACTION OF MANAGERIAL ABILITY AND CORPORATE GOVERNANCE REDUCES SUSTAINABILITY REPORTING - Yusuf, Dieza Risqi Ardila; Rohma, Frida Fanani (Universitas Airlangga, 2025)
This research aims to investigate the interaction effect of governance on the relationship between managerial ability and sustainability reporting in the banking industry in Indonesia. A green economy with social, environmental, and sustainability aspects is a substantial issue that is considered to have an impact on capital markets and foreign investment. Banking has a significant role in green financing to maintain environmental and financial stability. Thus, sustainable reporting is crucial for stakeholders as a sustainable green economy develops. This research uses quantitative methods involving banking data in Indonesia listed on the Indonesia Stock Exchange. The results of this research show that managerial ability can encourage sustainability reporting. Interestingly, the findings of this study show that corporate governance reduces the influence of managerial ability on sustainability reporting. Thus, the existence of good working principles does not mean that it can prevent individuals from rationalizing opportunistic actions. An organized instrumental climate in a governance system can be a double-edged sword that encourages individuals to optimize group interests by minimizing information disclosure to reduce disclosure costs.